Formulation of morning product using food residues - Padilha, Maria do Rosário de Fátima; Shinohara, Neide K. S.; Ferreira, Eron; Macedo, Indira M. E.; Machado, José; Carvalho-Neto, Pedro M. (Revista Geama, 2017)
In Brazil, there is resistance of the population to the use of stalks, leaves, peels and seeds of vegetables and fruits, leading to trash important parts of the food in good physiological conditions and with the presence of potential nutrients. In this research, a morning product was elaborated using green and dry coconut residue, jerimum and melon seed, crystallized sicilian lemon peel, cashew nut, common rapadura sweet and ginger. The bacteriological tests proved the hygienic-sanitary quality of the product, therefore suitable for consumption, that is, according to RDC 12/2001. It was also observed that the dehydration of all the residues reached the legal levels and accepted by ANVISA that limits in 25% the water content in the dehydrated foods. As for the centesimal composition, it was observed that the elaborated product with residues and other ingredients had a good content of macro nutrients. A use of the type of waste as a new food proposal constitutes an alternative to avoid and reduce: the serious environmental problem caused by the large residual volume generated, and the inadequate places in which they are stored or deposited, aggravating the scenario of food-borne pollutants.